IMPROVING INPATIENT SAFETY WITH ROLE MODEL DEVELOPMENT - Tanwiriah; Yanti, Noor Ridha; Negara, Candra Kusuma (Jurnal EduHealth, 2022)
Patients have a significant role to play in improving patient safety on their own. The active involvement of patients in planning, providing health services, and evaluating care can improve health services. This study aims to develop a model of the role of patients in improving patient safety in hospital inpatient rooms. This research is qualitative research with acan on research design. Participants in this study were 22 implementing nurses from 5 inpatient rooms. Using questionnaires, the data were collected using an online focus group discussion (FGD), observation sheets, field notes, and quantitative assessments. The data was analyzed using simple analytical and statistical content. This study resulted in 4 patient role models that can be used in the inpatient room and increased nurses' Knowledge about the role of patients in improving patient safety. The conclusions of this study show that the patient role model can be used as a reference in increasing the role of patients and reducing the occurrence of adverse events when patients are hospitalized so that patient safety can be achieved.